“Fertilización química y orgánica de tres variedades de café (Coffea arabica)” - Mejía Quintana, Limberth Alexander (2023)
In the research carried out at the Experimental Center Sacha Wiwa, belonging to the SEIC Foundation, La Maná canton, three doses of fertilizers applied to three varieties of coffee were evaluated. The proposed objectives were: to analyze the best dose of chemical and organic fertilization in coffee cultivation, to determine the effects of chemical and organic fertilizer on the agronomic behavior of the plant, and carry out an economic analysis of the costs per treatment. The experimental design was applied the Random Block Design, with a 3x4 factorial arrangement, corresponding to a mixture of chemical and organic fertilizers with different doses, each treatment consisted of four repetitions from which six experimental units were selected, the tabulation of Data was developed by means of Microsoft ® Office Excel version LTSC 2021 and for statistical análisis, the software of the University of Córdova, Infostat ®, which allows the interpretation of statistical data from generated variables. The Tukey method was used to contrast the data at 5% probability. With the use of chemical and organic products, it is considered highly profitable, due to the action that these microorganisms have in the unfolding of elements present in the fertilizers, without counting the environmental benefit that they have on plants, consumers, and the soil.